2016
DOI: 10.1080/0886022x.2016.1215221
|View full text |Cite
|
Sign up to set email alerts
|

The role of Silodosin as a new medical expulsive therapy for ureteral stones: a meta-analysis

Abstract: To evaluate the efficacy of Silodosin as a medical expulsive therapy of ureteral stones, we searched PubMed, EMBASE, the Cochrane Library, and CBM up to June 2015. All randomized controlled trials (RCTs) were identified in which patients were randomized to receive Silodosin versus placebo or other therapies for ureteral stones. Outcome measures assessed were overall stone expulsion rate (primary) and expulsion time, analgesics times, and the incidence of additional treatment and regarding treatment complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…Several previous systematic reviews and meta-analyses investigated silodosin versus tamsulosin for the treatment of ureteral stones [ 7 11 ]. The most recent study by Liu and colleagues [ 9 ] identified only five RCTs that yielded a pooled risk ratio of 1.25 (95% CI: 1.13 to 1.37), favoring silodosin over tamsulosin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous systematic reviews and meta-analyses investigated silodosin versus tamsulosin for the treatment of ureteral stones [ 7 11 ]. The most recent study by Liu and colleagues [ 9 ] identified only five RCTs that yielded a pooled risk ratio of 1.25 (95% CI: 1.13 to 1.37), favoring silodosin over tamsulosin.…”
Section: Discussionmentioning
confidence: 99%
“…For adverse events, we found no risk differences of common adverse effects, including headaches, dizziness, backache, nasal congestion, gastrointestinal effects, and postural hypotension, between silodosin and tamsulosin. By contrast, retrograde ejaculation was another common major side effect, and previous meta-analyses also showed that there was no significant difference between silodosin and tamsulosin in terms of retrograde ejaculation [ 7 11 ]. However, in the present meta-analysis, the results showed that silodosin may have a higher risk by 5% compared with tamsulosin for retrograde ejaculation, which contributed to higher total adverse events in the silodosin group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly studied primary endpoint was clearance or expulsion rate, which was successful passing of the stone. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] A summary of studies can be found in Table 2.…”
Section: Summary Of Studiesmentioning
confidence: 99%
“…9 There are published meta-analyses for each of the selective alpha-blockers (alfuzosin, silodosin, tamsulosin) and one that evaluated all alpha-blockers (selective and nonselective). [10][11][12][13] The tamsulosin meta-analysis included more than 2700 patients from 29 trials and found a 33% improvement in clearance rate with tamsulosin (0.2 mg and 0.4 mg daily) compared with control. Tamsulosin cleared stones more than calcium channel blockers (6 studies).…”
Section: Summary Of Studiesmentioning
confidence: 99%